EDUCAÇÃO PARA A HUMANIZAÇÃO - Levino Bertan; Vera Lúcia Soares de Araújo (Universidade do Oeste Paulista, 2011)
The theme aims to reflect about the structural obstacles that make difficult the education for humanization,such as, the predominance of the capitalist model, the inversion having to being, the instrumentalization of the human and the massification of culture. It points some solutions such as: revising the educational action aiming to understand the culture's phenomena and the and the influence in educational and social institutions, reflecting on the person's conscience and its place while a historical subject. The text show how is the way of the ethical values, the possibility of investing in training models that enhance a bigger view of the world, in other others, the holistic view, compromising with the society through the caress ethics.